Promoting Language and Cultural Diversity through the Mass Media: Views of Students at the University of Botswana - Jeremiah, Koketso (European Journal of Social Science Education and Research, 2016)
This study investigates the views of students at the University of Botswana as to whether or not the current situation in which the languages of ethnic minority groups in Botswana are marginalized or excluded for use in the national media such as television, radio and the Botswana Daily News, should continue or not. The study answered the following research questions: 1. What national television and radio stations exist in Botswana? 2. What programmes do these television and radio stations broadcast and with which languages? 3. Is the current situation of broadcasting with regard to the languages used for broadcasting fair, and, if not, what can be done to remedy the situation? It also addressed the following objectives:1. To identify the national television and radio stations which exist in Botswana? 2. To identify the programmes that the existing national television and radio stations broadcast and the languages used to broadcast those programmes. 3. To find out if the current system of broadcasting is fair in terms of the languages used and if it is not, to suggest some measures that can be taken to remedy the situation.The study used qualitative methods. Sampling was done by using purposive sampling. The data collection method used was a questionnaire. A sample of seven (7) students responded to the questionnaire. Three (3) or 43 percent said the current situation should continue while four (4) or 57 percent said it should be changed. The conclusion was that the current situation which marginalizes minority ethnic groups should be changed.